Factors Influencing the Quality and Reliability of Leaf Gas Exchange Measurements - Qing-Lai Dang (Recent Progress in Plant and Soil Research Vol. 3, 2021)
Measuring foliar gas exchange (photosynthesis, respiration, and transpiration) has become popular in a wide range of disciplinary fields because to the invention of portable gas exchange equipment. There are three common types of portable gas exchange systems: closed system, semi-closed system and open system. Modern instruments are simple to use and require little or no calibration by the operator. Indeed, some equipment can automatically create photosynthetic response curves to light and carbon dioxide. The ease of use and expanded capabilities of gas exchange instruments have substantially increased user confidence and the usage of gas exchange measurements both in field studies and research in enclosed environments. Measurement and calculation errors, however, are still possible. One paper submitted to a peer-reviewed journal, for example, reported net rates of photosynthesis with intercellular CO2 concentrations higher than the ambient CO2 concentration at the time of the observations. In my own lab, erroneous measurements have been noticed, particularly by inexperienced students. Errors can be caused by a variety of factors, including faulty equipment, inappropriate procedures, leaking leaf chambers, leaking or obstructed gas lines, or inadequate measurement conditions. Errors can also occur if the measurements are taken in the wrong order or at the wrong time for various treatments within the same study. Furthermore, even when studying the same species, data from multiple research are not necessarily comparable due to changes in measuring techniques or bases on which results are expressed (e.g., projected, hemi-surface and total surface leaf area). In this paper, I’ll go over some aspects of foliage gas exchange measurements that are either confusing or require special attention, including different types of instruments and their pros and cons.